PEMBENTUKAN PORTOFOLIO OPTIMAL PADA INDEKS LQ-45 DAN JII DENGAN MODEL MARKOWITZ SEBAGAI DASAR KEPUTUSAN INVESTASI - Syifa Adhani Mulya (2020)
The purpose of this research is to know the stocks that can be formed as a combination of the optimal portfolio with the proportion of funds of each shares by using Markowitz Model. The research was conducted on the stock indices LQ-45 and JII. The population that used in this research is the entire company listed on the LQ-45 stock index, which is 45 companies from February 2017 - July 2019 and on JII as many as 30 companies from June 2017 - November 2019. The results showed that there were 14 shares with portofolio expected return of 1.55% and a risk of 2.13% on the LQ-45 index and 10 shares on JII with portofolio expected return of 1.61% and a risk of 3.49% that could form as an optimal portfolio.